Ionospheric Response to 22-23 June 2015 Storm as Investigated Using Ground-Based Ionosondes and GPS Receivers Over India - Singh, Ram; Sripathi, S. (My University, 2017)
In this paper, we present response of equatorial and low-latitude ionosphere to 22/23 June 2015 geomagnetic storm using a chain of ground-based ionosondes located at Tirunelveli (8.73°N,77.70°E; geomagnetic latitude: 0.32°N), Hyderabad (17.36°N, 78.47°E; geomagnetic latitude: 8.76°N), and Allahabad (25.45°N, 81.85°E; geomagnetic latitude: 16.5°N) along with a chain of GPS receivers. Uniqueness of this storm is that in contrast to the equatorial plasma bubbles that were detected in the European sector, we see suppression of plasma bubbles in the Indian sector. The observations suggest that westward penetration electric field during local midnight caused abrupt decrease of virtual height (h’F (km)) to ~200 km and suppressed plasma bubbles due to undershielding. Later, the layer increased to 500 km simultaneously due to overshielding effect. On 23 June, we observed negative storm in the Northern Hemisphere while positive storm in the Southern Hemisphere. In addition, absence of equatorial Es layers at Tirunelveli and presence of F3 layer at Tirunelveli/Hyderabad seem to be associated with equatorial electrojet (EEJ)/counter electrojet (CEJ) variations. However, on 24 June, we observed strong negative storm effects at Allahabad/Hyderabad, while positive storm effect at Tirunelveli. Simultaneous enhancement of h’F (km) at all three ionosonde stations at 20:30 UT on 23 June during recovery phase suggest eastward disturbance dynamo (DD) electric field that caused presunrise spread F at Hyderabad/Allahabad but void of spread F at Tirunelveli suggesting its midlatitude origin. Periodogram analysis of foF2 and h’F (km) in the present analysis suggest the presence of shorter periods (~< 2 h) associated with prompt penetration (PP) electric fields while larger periods (>2 h) associated with DD electric field/winds.
Keywords: Ionosonde; Ionosphere; Plasma bubbles; Geomagnetic storm; Storms